Fungal coagulant for reduction of water turbidity - Al-Mamun, Abdullah; Jebun, Nessa; Alam, Md. Zahangir; Ahmad Raus, Raha (International Institute of Chemical, Biological & Environmental Engineering (IICBEE), 2016)
Turbidity from raw water is, usually, removed from by adding chemical coagulants. These chemicals are hazardous to human body and not much environmentally friendly. Therefore, this study was intended to discover microbial coagulant which would be a new replacement for the chemical coagulants. There are potential microorganisms, those can produce bioactive compounds, which can lead to different charges and surface properties. As such, the main goal of this project was to reduce turbidity of river water using natural coagulant. The discovered microbial coagulant showed promising results which can be considered as safe and environmentally friendly as compared to the conventional chemical coagulants. Thus far, a potential fungal strain is successfully identified which could reduce turbidity of water from 900 NTU to 54 NTU. It is expected that further optimization of the process parameters will help reduce the turbidity of the water. However, the full-scale application of the findings and the economic evaluation of the new coagulant is not determined yet.